The Entrepreneurship Development as an Alternative for Reduction of Poverty and Inequality Indices in Colombia (2013)
In Latin America there are huge problems of poverty and inequality that countries should solve establishing necessary public policies to overcome them. In Colombia this is a great proportion problem because most departments have these difficulties and that undoubtedly it creats an imbalance in the socio- economic conditions of the inhabitants of this country